The association of statins plus LDL receptor-targeted liposome-encapsulated doxorubicin increases in vitro drug delivery across blood-brain barrier cells (2012)
Background and PurposeThe passage of drugs across the blood-brain barrier (BBB) limits the efficacy of chemotherapy in brain tumours. For instance, the anticancer drug doxorubicin, which is effective against glioblastoma in vitro, has poor efficacy in vivo, because it is extruded by P-glycoprotein (Pgp/ABCB1), multidrug resistance-related proteins and breast cancer resistance protein (BCRP/ABCG2) in BBB cells. The aim of this study was to convert poorly permeant drugs like doxorubicin into drugs able to cross the BBB. Experimental ApproachExperiments were performed on primary human cerebral microvascular endothelial hCMEC/D3 cells, alone and co-cultured with human brain and epithelial tumour cells. Key ResultsStatins reduced the efflux activity of Pgp/ABCB1 and BCRP/ABCG2 in hCMEC/D3 cells by increasing the synthesis of NO, which elicits the nitration of critical tyrosine residues on these transporters. Statins also increased the number of low-density lipoprotein (LDL) receptors exposed on the surface of BBB cells, as well as on tumour cells like human glioblastoma. We showed that the association of statins plus drug-loaded nanoparticles engineered as LDLs was effective as a vehicle for non-permeant drugs like doxorubicin to cross the BBB, allowing its delivery into primary and metastatic brain tumour cells and to achieve significant anti-tumour cytotoxicity. Conclusions and ImplicationsWe suggest that our 'Trojan horse' approach, based on the administration of statins plus a LDL receptor-targeted liposomal drug, might have potential applications in the pharmacological therapy of different brain diseases for which the BBB represents an obstacle. © 2012 The Authors. British Journal of Pharmacology © 2012 The British Pharmacological Society.